Analyzing Factors Affecting the Effectiveness of Peer Assessment in EFL Teaching - Refanja Rahmatillah; Rizki Fajrita (Indonesian Journal of Teaching and Teacher Education, 2022)
The use of peer assessment in EFL teaching is increasing due to the focus shift from teacher-centered to student-centered approach. However, factors such as attitudes, motivation, language proficiency and relationship bias are believed to contribute to the effectiveness of peer assessment. This paper aims to analyze how the factors affect the effectiveness of peer assessment implementation in EFL teaching. The method used to analyze is a literature review by examining fifteen prior studies of peer assessment use in EFL context. It is found that there are three factors that affect the effectiveness of peer assessment implementation in EFL setting, which are students’ attitude and motivation, students’ English proficiency, and students’ relationship-bias. All these three factors can be interfered with teacher supports such as by describing the benefits of peer assessment to students, pairing the students with same-level of English proficiency, and applying anonymous evaluation. It is suggested that these three factors need to be carefully considered by teachers in EFL context in order to achieve the success of peer assessment implementation.